Safety and Efficacy of Intravenous Brivaracetam versus Levetiracetam in the Management of Status Epilepticus in Children: Intravenous Brivaracetam versus Levetiracetam in the Management of Status Epilepticus - Rahman, Ikram Ur; Ahmad, Muhammad Zubair; Tariq, Ali (Pakistan Journal of Health Sciences, 2026)
Status epilepticus (SE) is one of the most common pediatric neurological emergencies and a major cause of all pediatric epilepsy-related hospital admissions. Objectives: To compare the safety and efficacy of intravenous (IV) brivaracetam versus levetiracetam in the management of SE in children. Methods: This randomized controlled trial was performed at the Department of Pediatric Neurology, Institute of Child Health, Multan, Pakistan, from January to September 2025. A total of 152 children (76 in each group), aged 1 month to 16 years with SE, were randomly assigned to receive IV brivaracetam (2 mg/kg) or levetiracetam (40 mg/kg). Seizure cessation within 30 minutes of infusion, time to cessation, recurrence, hospitalization duration, and adverse events were documented. Data were analyzed using SPSS v26.0, with p<0.05 considered significant. Results: In a total of 152 children, the median age was 6.2 years (IQR 3.4–10.7), and 84 (55.3%) children were males. Seizure cessation within 30 minutes was noted in 65 (85.5%) children receiving brivaracetam and 55 (72.4%) receiving levetiracetam (p=0.047). The median time to cessation was 4.5 (IQR 3.0–7.0) minutes in bivarectam, vs. 6.0 (IQR 4.0–9.5) minutes with levetiracetam (p=0.009). The median hospital stay was 4.0 (IQR 3.0–6.0) days vs 5.5 (IQR 4.5–7.0) days (p=0.034) in brivarecetam and levetiracetam groups, respectively. Adverse events occurred in 10 (13.2%) children in the Bivaracetam group vs. 14 (18.4%) with levetiracetam (p=0.374), while no mortality was documented. Conclusions: IV brivaracetam achieves faster and more effective seizure cessation compared with levetiracetam in children with SE, with lower rates of adverse effects.